Judge Blaine Pettitt Retirement Luncheon at Fresno Hilton Hotel Ballroom - Watkins, Howard::::::::: (1985)
Judge Blaine Pettitt holding retirement gift of hand-engraved leather cowboy boots In background: Donald Fischbach, Judge Robert Mardikian, Mary Louise Frampton and ?